Ազգային երաժշտության հարցերը Խաչատուր Աբովյանի դիտարկումներում - Նավոյան, Մհեր (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Cуждения основополжника восточноармянского литературного языка Хачатура Абовяна о музыке строятся на идеях армянской национальной идентичности. Две его статьи, «Армянская церковная и народная музыка», как и несохранившаяся до наших дней статья, адресованная Императорской Российской академии, преследовали конкретную и осознанную цель определить характерные особенности идентичности армянского народа и познакомить с ними внешний мир. В истории армянской музыки эти статьи ознаменовали собой начало формирования национального мировоззрения, идеологические основы которого сложились под влиянием немецкого романтизма, и венцом которого явилось становление армянской национальной композиторской школы. The views of the founder of the Eastern Armenian literary language Khachatur Abovyan about music are based on the ideas of Armenian national identity. Two of his articles, "Armenian Church and Folk Music", as well as an article addressed to the Imperial Russian Academy that has not been preserved to this day, pursued a specific and cognitive goal to identify the characteristic features of the identity of the Armenian people and introduce them to the outside world. In the history of Armenian music, these articles marked the beginning of the formation of a national worldview, the ideological foundations of which were formed under the influence of German Romanticism, and the culmination of which was the formation of the Armenian national school of composers.
Keywords: Արվեստագիտություն